Administration, Marketing, Pharmacotherapy of Medicines in Neuro-Oncology - Shapovalova, Viktoriia (SSP Modern Pharmacy and Medicine, 2024)
Primary tumors make up 1.5% of all clinical cases. The most vulnerable group is children. Brain neoplasms are the second most common after acute leukemia. According to WHO statistics, men suffer 1.5 times more often than women. Administration, marketing, and pharmacotherapy of medicines in neuro-oncology were carried out. The administration of medicines for neuro-oncology pharmacotherapy in the USA and Ukraine was analyzed. Bevacizumab, Everolimus, Lomustine, Temozolomide were found to be approved in both countries. The issue of administration of medicines for neuro-oncology pharmacotherapy other than as prescribed by a doctor has been studied. The possibility of combined pharmacotherapy in neuro-oncology is indicated. Marketing studies of medicines for neuro-oncology pharmacotherapy have been conducted. The medicines are presented in different dosage forms: solutions for infusions, injections, capsules and lyophilisates. The manufacturers of these medicines are pharmaceutical companies from different countries: India, Germany, Austria, the Netherlands, Ukraine. The majority of medicinal products have indefinite registration in Ukraine, which indicates their availability on the pharmaceutical market for the treatment of neuro-oncological diseases. Causes of tumors, main histological groups of neoplasms, their degree of malignancy, symptoms of tumors, diagnostic methods, therapy and pharmacotherapy in neuro-oncology are given. Further research on the development of methods and preparations of pharmacotherapy for neuro-oncology is relevant and ongoing.